2009
DOI: 10.1136/qshc.2007.022335
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and procedure-specific risk factors for postoperative complications in peripheral vascular surgery

Abstract: A former CVA and acute surgery were independent risk factors of postoperative complications. Identifying the cause and consequence of each complication is essential in a complication registration. When using complications as an indicator of quality of care in this population, an adjustment should be made for patient comorbidity and surgical indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The risk of postoperative AEs is directly related to preoperative general health status and presence of severe comorbidity. 26 Reports have also confirmed that patients undergoing LEAR have an increased risk of perioperative cardiac AEs. 27,28 Limb salvage.…”
Section: Functional Status Prior Lear: Ambulatory Vs Nonambulatorymentioning
confidence: 85%
“…The risk of postoperative AEs is directly related to preoperative general health status and presence of severe comorbidity. 26 Reports have also confirmed that patients undergoing LEAR have an increased risk of perioperative cardiac AEs. 27,28 Limb salvage.…”
Section: Functional Status Prior Lear: Ambulatory Vs Nonambulatorymentioning
confidence: 85%
“…[6][7][8][9] In our nationwide analysis of over two hundred thousand patients who underwent surgery for colorectal cancer, patients with diabetes had a lower mortality than those without diabetes. Ninety three percent of the diabetic population had uncomplicated diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Diabetic patients often have microvascular and marcrovascular pathology 4 that influences their perioperative course 5 and have a significantly higher risk of perioperative infection and post operative cardiovascular morbidity and mortality. [6][7][8][9] Hyperglycemia may be the underlying factor that mediates worse outcomes in diabetics. The association between hyperglycemia and infection has been long recognized; studies report diverse defects in neutrophil and monocyte dysfunction such as adherence, chemotaxis and phagocytosis, 10,11 while improvement in blood sugars helps restore granulocyte function.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established that diabetic patients are at a higher risk of developing complications after surgery, 14,15 and perioperative hyperglycemia may be the determining factor. 16,17 High blood glucose levels negatively affect the mobilization and phagocytotic ability of neutrophils and monocytes, predisposing to infection.…”
Section: Discussionmentioning
confidence: 99%